Upaya Pengembangan Industri Kecil untuk Keberlangsungan Usaha (Studi terhadap pengembangan Sentra Industri Tempe Sanan, Kota Malang) - Endarto, Karuniawan Andre (Jurnal Administrasi Publik, 2014)
Abstract: Small Industrial Development Efforts for Business Sustainability (Case on development of Sentra Industri Tempe Sanan, Malang City).The development of industry chips tempe Sanan done because the food that which overflows and to deal with financial management business limited.Research is aimed to know and described the effort as well as the impediment to the development of industry and supporters in the activities of crackers tempe Sanan through the related agencies.This type of research is research usedresearch descriptive with a qualitative approach.Efforts to the development of industry chips tempe sanan focused on capital, facilitate them the development of capital, the development of human resources ( HRD ) and facilitate them marketing.Development activities carried out by the City Government through the hapless Department of industry and trade, Department of cooperatives and SMEs, Implementing Financial Partners Bank technical consultants, as well as the entrepreneurs themselves.Supporting factors are some of the attitudes of employers are cooperative, tourist destination,the formation of industrial centers, as well as supporting institutions there. While the factors restricting in an effort industry development chips tempe Sanan, among other: limitations employees departments, the building time improper, infrastructure parking minim and prices of imported soybeans are not stable. Advice from researcher is development industry chips tempe Sanan should be developed to become tourism education about tempe and chips tempe. Keywords: efforts, industry development, industry tempe chips Sanan Abstrak: Upaya Pengembangan Industri Kecil untuk Keberlangsungan Usaha (Studi terhadap pengembangan Sentra Industri Tempe Sanan, Kota Malang). Pengembangan industri keripik tempe Sanan dilakukan karena tempe yang melimpah dan untuk mengatasi manajemen keuangan usaha yang terbatas. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan upaya serta faktor penghambat dan pendukung dalam kegiatan pengembangan industri keripik tempe Sanan. Jenis penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif.Upaya pengembangan industri keripik tempe Sanan berfokus pada fasilitasi permodalan, pengembangan permodalan, pengembangan sumber daya manusia (SDM) dan fasilitasi pemasaran. Kegiatan pengembangan dilakukan oleh Pemerintah Kota Malang melalui Dinas Perindustrian dan Perdagangan, Dinas Koperasi dan UKM, Unit Pelaksana Teknis Konsultan Keuangan Mitra Bank, serta pengusaha itu sendiri.Faktor pendukungnya adalah beberapa sikap pengusaha yang kooperatif, daerah tujuan wisata, terbentuknya sentra industri, serta terdapat lembaga pendukung. Sedangkan faktor penghambatnya antara lain: keterbatasan pegawai dinas, waktu pembinaan yang tidak tepat, infrastruktur parkir yang minim dan ketidakstabilan harga kedelai import. Saran dari peneliti adalah pengembangan industri keripik tempe Sanan sebaiknya dikembangkan menjadi kampung wisata edukasi tempe dan keripik tempe. Kata Kunci: Upaya, pengembangan industri, industri keripik tempe Sanan.